Challenges in ultrafast transient absorption using reflection mode. - Leung, Ho Fai. (2012)
Transient Absorption Spectroscopy in reflection mode is a less explored field in the area of ultrafast spectroscopy. Upon initial investigations into Differential Reflection Spectra (DRS) on poly(3-hexylthiophene) (P3HT) samples , several problems were found to arise. These problems include inconsistent spectra shapes and non-Differential Transmission Spectra (DTS)-like spectra, which would have implications on our way of interpreting any data taken from said spectra. In this work, we explore possible causes for these spectra shapes as well as possible methods of resolution. We explore various parameters such as the thickness of the active layer, the systematic variation of the angle of incidence, the presence of excessive contaminants and the use of plasma treatment. We find that the thickness of the sample used, amongst other factors, plays a heavy role in determining the probability of obtaining DTS-like spectra. This is attributed to the fact that varying the thickness also varies the optical path difference for components of the probe beam reflected off the Aluminium-P3HT interface and the P3HT-PEDOT:PSS interface, thus leading to varying interference effects. The use of plasma treatment, enabling greater adhesion, increases the chances of obtaining consistent spectral shapes from identical samples. Hence, with careful control of thickness and plasma treatment, systematic studies of transient absorption (TA) spectra are possible.